Fluorescence microscopy characterization in the study of addiction-related neuronal circuits : Master’s thesis - Hornnaess, Helene (My University, 2024)
Despite significant advances in understanding addiction, the precise mechanisms driving individual susceptibility and neural alterations facilitating compulsive drug use remain incompletely understood. This study aimed to fill part of this gap by investigating the optimal virus expression time for the GCaMP8 calcium indicator biosensor, including sex differences in expression levels and potential neurotoxicity. GCaMP8 was delivered via adeno-associated virus (AAV) to the nucleus accumbens (NAc) and prefrontal cortex (PFC) in male and female C57Bl/6J mice, allowing real-time monitoring of calcium dynamics and neuronal activity related to cocaine administration. GCaMP8m and AAV were chosen for their efficiency and specificity in labelling neurons and lower toxicity, essential for long-term studies. Results showed no significant sex differences in viral transfection, with stable expression levels over time. However, females exhibited a decline in expression, suggesting potential sex-specific factors. The study also highlighted that viral expression quality and fiber tip placement significantly influence fiber photometry recordings. While good viral expression is crucial, it alone does not ensure high-quality recordings. Occasionally, satisfactory recordings were obtained despite suboptimal viral expression or fiber placement, likely due to optimal recording conditions and compensatory mechanisms such as synaptic plasticity and neurotransmitter release alterations. In conclusion, these insights refine fiber photometry techniques for studying drug addiction, emphasizing the interplay between viral expression, fiber placement, and recording conditions. This contributes to more insights in neuropsychiatric research, particularly in substance use disorders. This project was a collaboration between the Laboratory of Neuropsychiatry at Region Hovedstaden and the Kohlmeier Laboratory at the Department of Drug Design and Pharmacology, University of Copenhagen.
Keywords: Fluorescence imaging, histology, reward system, cocaine addiction, GCAMP8